Medición De Carga Mental De Trabajo En La Industria Automotriz En México - Rivera, Miguel Macías; Romero, Raúl Rocha (European Scientific Journal, ESJ, 2016)
The primary objective of this research was to determine and show the relationship that exists between the mental workload perceived by personnel in the automotive assembly industry and the labor activity performed. The sample was constituted of fifty-six workers and the evaluation consisted of the application of the SCAM Test (Díaz, Hernández, Rolo, Galván, Fraile and Loayssa, 2009), in the employee´s workplace, as well as observation of the activities performed and interviews with some of the workers. This instrument evaluates five dimensions of workload: cognitive demands and information complexity, health consequences for workers, task characteristics, temporal organization of work and work rate. Results show that professionals perceive higher levels of mental workload, in the dimensions of cognitive demands, task complexity, as well as characteristics of the task. In addition to these findings, technicians perceived higher levels in work rate and corresponding health consequences. There is also a relationship between demographic and labor characteristics with the mental load perceived in workers. Furthermore, the environmental characteristics at work were not a significant factor in the perception of mental load in this research.